Workshop report: national planning or phase 1 of the CCAC paddy rice component in Bangladesh - Rahman S; Sander, Björn Ole (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
This workshop was conducted as part of the mitigation strategies in rice production project, implemented with support from the agriculture initiative of the Climate and Clean Air Coalition. The project is carried out in Bangladesh, Columbia, and Vietnam with the CGIAR Research Program on Climate Change, Agriculture and Climate Change (CCAFS), the International Rice Research Institute (IRRI), and leading research and agriculture organizations in Vietnam.